Applications of Some Generalized Janowski Meromorphic Multivalent Functions. (26th July 2021) - Ahmad, Bakhtiar; Khan, Muhammad Ghaffar; Darus, Maslina; Khan Mashwani, Wali; Arif, Muhammad
Abstract : In this article, the ideas of post-quantum calculus and meromorphic multivalent functions are combined and some applications of these functions are discussed. We introduce a new subclass of meromorphic multivalent functions in association with Janowski domain. We investigate and study some useful geometric properties of this class of functions such as sufficiency criteria, distortion problem, growth theorem, radii of starlikeness and convexity, convex combination, and coefficient estimates for this class.